ADULT EDUCATION IN IRELAND AND UKRAINE: COMMON AND DISTINCTIVE FEATURES IN THE TRENDS OF DEVELOPMENT - Terentieva, Nataliia O.; Sytnyk, Olha I. (Educological discourse, 2016)
In the article adult education development in Ireland and Ukraine is described, the comparative analysis of current trends of adult education development in Ireland and Ukraine is given, the characteristics of basic forms and content of adult education in both countries is examined. On the basis of the study authors make the effort to find out common and different in Irish adult education to Ukraine and form recommendations for the use of progressive ideas of the Irish experience in developing the system of adult education in Ukraine.